STUDI ETNOFARMASI TUMBUHAN BERKHASIAT OBAT PADA SUKU BANGGAI DI KABUPATEN BANGGAI LAUT, PROVINSI SULAWESI TENGAH - Nur Khairiyah; Syariful Anam; Akhmad Khumaidi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2016)
A study of nutritious herbs etnopharmacy has been done to Banggai ethnic from March to June 2015 in Banggai Laut Regency, Central Sulawesi. This research aims at identifying every kind of herbs parts used as traditional medicine, types of diseases cured using herbs by Banggai ethnic in Banggai Laut Regency, and the percentage of the usage by the informant about herbs as a traditional medicine. This is a descriptive research that uses qualitative method and take the sample purposively through open-ended interview involved 7 informants asked by questionnaire. The result of this research revealed that there are 54 types of herbs divided into 31 family used as medicine. The most widely used herbs is from 5 species of Zingiberaceae family and Lamiaceae family. Interview result revealed that there are 10 types of chronic diseases, 3 infectious diseases, non-communicable diseases 27, and 5 used for health care body. The parts of herbs used are leaf (49 percent), stem, sap, fruit, rhizomes, roots, tubers, herbs and bark. The Banggai ethnic precede the herbs through boiled, mashed, squeezed, shredded, soaked, brewed and then consumed, drunk, rubbed, pasted, applied directly. Processing methods most often done is boiled and drunk the herbs straightly. The higher belief the society has in the herbs ability to cure the diseases the higher use of herbal medicine as an alternative of diseases healing.